Therapeutic Dilemmas Faced When Managing a Life-Threatening Presentation of a Myocardial Bridge - Debbie Falconer; Sariha Yousfani; Anna S. Herrey; Pier Lambiase; Gabriella Captur (Case Reports in Cardiology)
Background. Myocardial bridges are congenital abnormalities, where a segment of coronary artery travels intramyocardially, rather than the typical epicardial course. The overlying muscle segment is termed “the bridge”. Most myocardial bridges are asymptomatic, but some can result in myocardial ischaemia, arrhythmias, and sudden cardiac death. Case Presentation. A 31-year-old male with no past medical history presented to our tertiary cardiac centre following an out-of-hospital ventricular fibrillation arrest. Coronary angiography and computed tomography of the coronary arteries revealed a 2 cm myocardial bridge overlying the left anterior descending (LAD) artery. An exercise echocardiogram demonstrated severe apical ballooning and hypokinesis during peak exercise, with corresponding ST-segment elevation, resolving on rest. Options for medical therapy of a symptomatic myocardial bridge include beta blockers, calcium channel blockers, ivabradine, or a combination thereof. Surgical interventions include deroofing the bridge and revascularisation of the affected region with bypass grafting. However, a lack of trial data comparing medical regimens and surgical interventions makes it difficult to ascertain the most effective management strategy for each patient. There was disagreement between experts at different tertiary centres over the optimal management of this patient. He was treated with multiple regimes of medical therapy with ongoing ischaemia on stress testing, before undergoing a negative stress test on amlodipine, diltiazem, and isosorbide mononitrate. It was felt that no further intervention was necessary at this time given his exercise test was now negative for ischaemia. However, after seeking a second opinion, he underwent surgical intervention with bypass grafting of his left anterior descending artery, followed by implantation of an implantable cardiac defibrillator. Subsequently, an angiogram postsurgery demonstrated concomitant spasm of the LAD and he was resumed on medical therapy with calcium channel blockers and nitrates. Discussion. Without randomised trials, it is impossible to determine the optimal management strategy for each patient. It is possible that some patients with myocardial bridges are not being trialled on optimal medical therapy prior to undergoing invasive and irreversible interventions.